An establishment of the role of private and public sector interests in the context of tourism transport planning and development: the case of Malaysia - Cheuk, Sharon Choy Sheung; Liew, Janie Tsonis; Phang, Grace Ing; Izyanti Awang Razli (The Clute Institute,Estelle van Tonder, Ph.D, 2010)
Although 90% of the tourism industry consists of small businesses, the approach of consecutive governments in Malaysia is that tourism has reached a stage where its promotion and funding is the responsibility of the private sector. When national and regional tourist promotional boards were established, it was the intention that these would act as a vehicle for cooperation between the public and private sectors. This has proved to be extremely optimistic, with only a small number of tourism businesses actually joining in the decision-making processes of the direction for tourism development. The role of tourism development has been further undermined with the increasing rate of tourist arrivals, further implicating the control of public-sector resources, while governments place reliance on private/public partnerships as the model for the future. This research paper reports on the findings of a two-year study on the promotion of transportation in tourism development in Malaysia. It establishes the role of private and public sector interests in the context of tourism transport planning and development. A qualitative approach to in-depth interviews was conducted with respondents from the public sector (policy makers and local authority and government agency representatives) and the private sector (tour and travel agents) in Malaysia. The empirical evidence has shown that implementing stakeholders within the tourism industry are receptive to the promotion of transportation and aware of the differing roles each sector plays in the context of tourism transport planning and development. However, they do not fully exploit the complementary role played by the other sector for mutual benefit via consultations and public private partnerships at the planning stage.